PKM SOSIALISASI DAN EDUKASI DETERJEN RAMAH LINGKUNGAN DI LINGKUNGAN SEKOLAH DAN KELURAHAN SUKATANI TAPOS DEPOK - Anik Pujiati; Kasih Haryo Basuki; Nurdeni Nurdeni (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Environmental problems are global problems that require a helping hand from all the people of the earth. Water, air and land pollution is increasing due to human behavior. Detergent in everyday life is a basic need for all citizens. Sometimes people do not feel guilty if it turns out that detergent waste can contribute to environmental pollution. Even though there have been many discoveries and journals that discuss the damage caused and there are other alternatives that are more environmentally friendly. So, this community service program aims to provide education and outreach about environmentally friendly detergents that are also pocket friendly. By practicing together to make detergent like this, it is hoped that PKK women can apply the knowledge they have gained so that they can make their own detergent according to their needs and also an environmentally friendly detergent. People can save more and their waste products are also safe and reduce environmental pollution